Intralesional injection of OK-432 in cystic hygroma - Hazim, Muhammad Y S; Moses, Shamina Sara; Tang, Ing Ping (Malaysian Medical Association, 2016)
Background: Lymphangiomas are congenital malformations of the lymphatic system with characteristic dilated endothelium-lined spaces. It is vulnerability to infection or chemical irritants cause spontaneous reduction in size and in some cases complete resolution. Intralesional injection of OK-432 or Picibanil (lyophilized incubation mixture of Group A Streptococcus pyogenes of human origin) is slowly gaining recognition as its safety and efficacy standards have shown to avoid complications resulting from surgical interventions. The objective of this study was to evaluate the clinical outcomes of cystic hygroma patients who received OK-432 injections. Methods: In between 2011 and 2013, six patients with cystic hygroma received intralesional injection of OK-432. All the patients were assessed clinically and radiologically either via ultrasound, computer tomography (CT) or magnetic resonant imaging (MRI) prior to and after receiving the injections. Patients’ response towards treatment was classified as total shrinkage, marked shrinkage (greater than 50% reduction in size), slight shrinkage (less than 50% reduction in size) or non-responsive to treatment. Results: Mean duration of follow-up was 12 months. Total shrinkage was achieved in one patient, marked shrinkage in three patients and one patient experienced mild shrinkage. Only one out of the six patients showed no response to treatment. None of the patients in this study experienced serious complications or adverse effects post intralesional injection of OK-432. Conclusions: Intralesional OK-432 injection is an effective and safe alternative in treating cystic hygroma